Bongalong : marketing cannabis products in a stigmatized environment - Scadron, Travis E., (SAGE Knowledge. Cases., 2018)
Bongalong is a small company operating in an industry that is emerging worldwide and is poised to grow exponentially in South Africa with the emergence of new cannabis policy. However, there are barriers in the market which they need to address. The case demonstrates the challenges of operating in an emerging industry as well as the characteristics that are necessary to succeed in such a space. More importantly, the case points to the role of economic, political, and social context and the role each of them plays in analysing how to best operate in an industry that is not fully formed. The case looks at operating in stigmatised industries and explores the social factors that create stigma.